Zebrafish as an emerging tool for drug discovery and development for thyroid diseases. Issue 130 (November 2022) - Yadav, Poonam; Sarode, Lopmudra P.; Gaddam, Ravinder Reddy; Kumar, Puneet; Bhatti, Jasvinder Singh; Khurana, Amit; Navik, Umashanker
Abstract: Zebrafish is a useful model for understanding human genetics and diseases and has evolved into a prominent scientific research model. The genetic structure of zebrafish is 70% identical to that of humans. Its small size, low cost, and transparent embryo make it a valuable tool in experimentation. Zebrafish and mammals possess the same molecular mechanism of thyroid organogenesis and development. Thus, thyroid hormone signaling, embryonic development, thyroid-related disorders, and novel genes involved in early thyroid development can all be studied using zebrafish as a model. Here in this review, we emphasize the evolving role of zebrafish as a possible tool for studying the thyroid gland in the context of physiology and pathology. The transcription factors nkx2.1a, pax2a, and hhex which contribute a pivotal role in the differentiation of thyroid primordium are discussed. Further, we have described the role of zebrafish as a model for thyroid cancer, evaluation of defects in thyroid hormone transport, thyroid hormone (TH) metabolism, and as a screening tool to study thyrotoxins. Hence, the present review highlights the role of zebrafish as a novel approach to understand thyroid development and organogenesis. Graphical abstract: Image 1 Highlights: Like mammals, zebrafish also possess the hypothalamus-pituitary-thyroid axis. Thyroid hormone signaling is regulated by the hypothalamus-pituitary axis, deiodinases, and transporters. Zebrafish is an evolving model to study thyroid hormone signaling and related disorders. Zebrafish model could be utilized for discovering novel therapeutic tools.